2021
DOI: 10.3389/fpsyg.2021.565516
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of COVID-19 Confinement on Anxiety, Sleep and Executive Functions of Children and Adolescents in Spain

Abstract: Children and adolescents are not indifferent to the dramatic impact of the COVID-19 pandemic, and the need to be forced to live in confinement. The change in life to which they have been abruptly subjected forces us to understand the state of their mental health in order to adequately address both their present and future needs. The present study was carried out with the intention of studying the consequences of confinement on anxiety, sleep routines and executive functioning of 1,028 children and adolescents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
84
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 70 publications
14
84
0
3
Order By: Relevance
“…The lack of regular social interaction [ 11 , 12 ], decreased physical activity level [ 13 , 14 ], and more electronic screen time [ 15 , 16 ] were all considered as the contributors to poor sleep quality and mental disturbance, and when combined with such a major public health event-the COVID-19 outbreak, were expected to induce remarkable changes in sleep and psychological health in the short and long term [ 7 , [17] , [18] , [19] ]. In line with these predictions, several cross-sectional and qualitative studies from different countries revealed a high prevalence of anxiety and depression in confined adolescents [ [20] , [21] , [22] , [23] ]. A longitudinal study, in which 1339 adolescents aged between 9 and 18 from three countries (USA, Netherlands, Peru) were recruited, indicated that the symptoms of depression significantly increased during the pandemic, whereas the symptoms of anxiety remained unchanged [ 24 ].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…The lack of regular social interaction [ 11 , 12 ], decreased physical activity level [ 13 , 14 ], and more electronic screen time [ 15 , 16 ] were all considered as the contributors to poor sleep quality and mental disturbance, and when combined with such a major public health event-the COVID-19 outbreak, were expected to induce remarkable changes in sleep and psychological health in the short and long term [ 7 , [17] , [18] , [19] ]. In line with these predictions, several cross-sectional and qualitative studies from different countries revealed a high prevalence of anxiety and depression in confined adolescents [ [20] , [21] , [22] , [23] ]. A longitudinal study, in which 1339 adolescents aged between 9 and 18 from three countries (USA, Netherlands, Peru) were recruited, indicated that the symptoms of depression significantly increased during the pandemic, whereas the symptoms of anxiety remained unchanged [ 24 ].…”
Section: Introductionmentioning
confidence: 58%
“…The cross-sectional COVID-19 studies have also demonstrated the relationship between the change of mental health and sleep due to the COVID-19 pandemic [ 21 , 26 , [33] , [34] , [35] , [36] ]. For instance, Hyun, Hahm [ 33 ] reported that the symptoms of depression and anxiety explained poor sleep quality in young adults during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in Spanish children’s lifestyles have affected many aspects of their lives, increasing their sedentary behaviors [ 30 ], decreasing physical activity [ 31 ], and even producing changes in their mental health [ 32 ]. According to our results, children’s vision has been also affected, with a decrease in the hyperopia rates, an increase in the emmetropia rates, and a decrease in the mean value of SE in children examined in 2020 when compared to 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive skills, which develop in parallel with periodic maturation, push adolescents toward new evaluations and abstractions concerning both themselves and their environment (Lavigne-Cerván et al, 2021 ). Adolescence can also be a period of depression, anger, conflict, and anxiety (Ellis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%